Modern Approaches to the Medical Use of pH- and Temperature-Sensitive Copolymer Hydrogels (Review) - Vyacheslav A. Kuznetsov; Petr O. Kushchev; Irina V. Ostankova; Alexander Yu. Pulver; Natalia A. Pulver; Stanislav V. Pavlovich; Rimma A. Poltavtseva (Kondensirovannye sredy i mezhfaznye granitsy = Condensed Matter and Interphases, 2020)
This article provides the review of the medical use of pH- and temperature-sensitive polymer hydrogels. Such polymers are characterised by their thermal and pH sensitivity in aqueous solutions at the functioning temperature of living organisms and can react to the slightest changes in environmental conditions. Due to these properties, they are called stimuli-sensitive polymers. This response to an external stimulus occurs due to the amphiphilicity (diphilicity) of these (co)polymers. The term hydrogels includes several concepts of macrogels and microgels. Microgels, unlike macrogels, are polymer particles dispersed in a liquid and are nano- or micro-objects. The review presents studies reflecting the main methods of obtainingsuch polymeric materials, including precipitation polymerisation, as the main, simplest, and most accessible method for mini-emulsion polymerisation, microfluidics, and layer-by-layer adsorption of polyelectrolytes. Such systems will undoubtedly be promising for use in biotechnology and medicine due to the fact that they are liquid-swollen particles capable of binding and carrying various low to high molecular weight substances. It is also important that slight heating and cooling or a slight change in the pH of the medium shifts the system from a homogeneous to a heterogeneous state and vice versa. This providesthe opportunity to use these polymers as a means of targeted drug delivery, thereby reducing the negative effect of toxic substances used for treatment on the entire body and directing the action to a specific point. In addition, such polymers can be used to create smart coatings of implanted materials, as well as an artificial matrix for cell and tissue regeneration, contributing to a significant increase in the survival rate and regeneration rate of cells and tissues. References 1. Gisser K. R. C., Geselbracht M. J., Cappellari A.,Hunsberger L., Ellis A. B., Perepezko J., et al. Nickeltitaniummemory metal: A "Smart" material exhibitinga solid-state phase change and superelasticity. Journalof Chemical Education. 1994;71(4): 334. DOI: https://doi.org/10.1021/ed071p3342. Erman B., Flory P.J.. Critical phenomena andtransitions in swollen polymer networks and in linearmacromolecules. Macromolecules. 1986;19(9): 2342–2353. DOI: https://doi.org/10.1021/ma00163a0033. Tanaka T., Fillmore D., Sun S.-T., Nishio I.,Swislow G., Shah A. Phase transitions in ionic gels.Physical Review Letters. 1980;45(20): 1636–1639. DOI:https://doi.org/10.1103/physrevlett.45.16364. Polymer Gels. DeRossi D., Kajiwara K., Osada Y.,Yamauchi A. (eds.). Boston, MA: Springer US; 1991.354 p. DOI: https://doi.org/10.1007/978-1-4684-5892‑35. Ilmain F., Tanaka T., Kokufuta E. Volumetransition in a gel driven by hydrogen bonding. Nature.1991;349(6308): 400–401. DOI: https://doi.org/10.1038/349400a06. Kuhn W., Hargitay B., Katchalsky A., EisenbergH. Reversible dilation and contraction by changing thestate of ionization of high-polymer acid networks.Nature. 1950;165(4196): 514–516. DOI: https://doi.org/10.1038/165514a07. Steinberg I. Z., Oplatka A., Katchalsky A.Mechanochemical engines. Nature. 1966;210(5036):568-571. DOI: https://doi.org/10.1038/210568a08. Tian H., Tang Z., Zhuang X., Chen X., Jing X.Biodegradable synthetic polymers: Preparation,functionalization and biomedical application. Progressin Polymer Science. 2012;37(2): 237–280. DOI: https://doi.org/10.1016/j.progpolymsci.2011.06.0049. Gonçalves C., Pereira P., Gama M. Self-Assembledhydrogel nanoparticles for drug delivery applications.Materials. 2010;3(2): 1420–1460. DOI: https://doi.org/10.3390/ma302142010. Pangburn T. O., Petersen M. A., Waybrant B.,Adil M. M., Kokkoli E. Peptide- and Aptamer-functionalizednanovectors for targeted delivery of therapeutics.Journal of Biomechanical Engineering. 2009;131(7):074005. DOI: https://doi.org/10.1115/1.316076311. Caldorera-Moore M. E., Liechty W. B., PeppasN. A. Responsive theranostic systems: integrationof diagnostic imaging agents and responsive controlledrelease drug delivery carriers. Accounts of ChemicalResearch. 2011;44(10): 1061–1070. DOI: https://doi.org/10.1021/ar200177712. Das M., Sanson N., Fava D., Kumacheva E.Microgels loaded with gold nanorods: photothermallytriggered volume transitions under physiologicalconditions†’. Langmuir. 2007;23(1): 196–201. DOI:https://doi.org/10.1021/la061596s13. Oh J. K., Lee D. I., Park J. M. Biopolymer-basedmicrogels/nanogels for drug delivery applications.Progress in Polymer Science. 2009;34(12): 1261–1282.DOI: https://doi.org/10.1016/j.progpolymsci.2009.08.00114. Oh J. K., Drumright R., Siegwart D. J.,Matyjaszewski K. The development of microgels/nanogels for drug delivery applications. Progress inPolymer Science. 2008;33(4): 448–477. DOI: https://doi.org/10.1016/j.progpolymsci.2008.01.00215. Talelli M., Hennink W. E. Thermosensitivepolymeric micelles for targeted drug delivery.Nanomedicine. 2011;6(7): 1245–1255. DOI: https://doi.org/10.2217/nnm.11.9116. Bromberg L., Temchenko M., Hatton T. A. Smartmicrogel studies. Polyelectrolyte and drug-absorbingproperties of microgels from polyether-modifiedpoly(acrylic acid). Langmuir. 2003;19(21): 8675–8684.DOI: https://doi.org/10.1021/la030187i17. Vinogradov S. V. Polymeric nanogel formulationsof nucleoside analogs. Expert Opinion on Drug Delivery.2007;4(1): 5–17. DOI: https://doi.org/10.1517/17425247.4.1.518. Vinogradov S. V. Colloidal microgels in drugdelivery applications. Current Pharmaceutical Design.2006;12(36): 4703–4712. DOI: https://doi.org/10.2174/13816120677902625419. Kabanov A. V., Vinogradov S. V. Nanogels aspharmaceutical carriers: finite networks of infinitecapabilities. Angewandte Chemie International Edition.2009;48(30): 5418–5429. DOI: https://doi.org/10.1002/anie.20090044120. Lee E. S., Gao Z., Bae Y. H. Recent progress intumor pH targeting nanotechnology. Journal ofControlled Release. 2008;132(3): 164–170. DOI: https://doi.org/10.1016/j.jconrel.2008.05.00321. Dong H., Mantha V., Matyjaszewski K.Thermally responsive PM(EO)2MA magnetic microgelsvia activators generated by electron transfer atomtransfer radical polymerization in miniemulsion.Chemistry of Materials. 2009;21(17): 3965–3972. DOI:https://doi.org/10.1021/cm901143e22. Nayak S., Lyon L. A. Soft nanotechnology withsoft nanoparticles. Angewandte Chemie InternationalEdition. 2005;44(47): 7686–7708. DOI: https://doi.org/10.1002/anie.20050132123. Hennink W. E., van Nostrum C. F. Novelcrosslinking methods to design hydrogels. AdvancedDrug Delivery Reviews. 2012;64: 223–236. DOI: https://doi.org/10.1016/j.addr.2012.09.00924. Motornov M., Roiter Y., Tokarev I., Minko S.Stimuli-responsive nanoparticles, nanogels and capsulesfor integrated multifunctional intelligent systems.Progress in Polymer Science. 2010;35(1-2): 174–211. DOI:https://doi.org/10.1016/j.progpolymsci.2009.10.00425. Saunders B. R., Laajam N., Daly E., Teow S.,Hu X., Stepto R. Microgels: From responsive polymercolloids to biomaterials. Advances in Colloid andInterface Science. 2009;147-148: 251–262. DOI: https://doi.org/10.1016/j.cis.2008.08.00826. Landfester K. Miniemulsion polymerizationand the structure of polymer and hybrid nanoparticles.chemInform. 2009;40(33). DOI: https://doi.org/10.1002/chin.20093327927. Seo M., Nie Z., Xu S., Mok M., Lewis P.C.,Graham R., et al. Continuous microfluidic reactors forpolymer particles. Langmuir. 2005;21(25): 11614–11622. DOI: https://doi.org/10.1021/la050519e28. Nie Z., Li W., Seo M., Xu S., Kumacheva E. Janusand ternary particles generated by microfluidicsynthesis: design, synthesis, and self-assembly. Journalof the American Chemical Society. 2006;128(29): 9408–9412. DOI: https://doi.org/10.1021/ja060882n29. Seiffert S., Thiele J., Abate A. R., Weitz D. A.Smart microgel capsules from macromolecularprecursors. Journal of the American Chemical Society.2010;132(18): 6606–6609. DOI: https://doi.org/10.1021/ja102156h30. Rossow T., Heyman J. A., Ehrlicher A. J.,Langhoff A., Weitz D. A., Haag R., et al. Controlledsynthesis of cell-Laden Microgels by Radical-FreeGelation in Droplet Microfluidics. Journal of theAmerican Chemical Society. 2012;134(10): 4983–4989.DOI: https://doi.org/10.1021/ja300460p31. Perry J. L., Herlihy K. P., Napier M. E.,DeSimone J. M. PRINT: A novel platform toward shapeand size specific nanoparticle theranostics. Accountsof Chemical Research. 2011;44(10): 990–998. DOI:https://doi.org/10.1021/ar200031532. Caruso F., Sukhorukov G. Coated Colloids:Preparation, characterization, assembly and utilization.In: Decher G., Schlenoff J. B., editors. MultilayerThin Films. Weinheim, FRG: Wiley-VCH Verlag GmbH& Co. KGaA; 2002. p. 331-362.33. Sauzedde F., Elaïssari A., Pichot C. Hydrophilicmagnetic polymer latexes. 2. Encapsulation ofadsorbed iron oxide nanoparticles. Colloid & PolymerScience. 1999;277(11): 1041–1050. DOI: https://doi.org/10.1007/s00396005048834. Sauzedde F., Elaïssari A., Pichot C. Hydrophilicmagnetic polymer latexes. 1. Adsorption of magneticiron oxide nanoparticles onto various cationic latexes.Colloid & Polymer Science. 1999;277(9): 846–855. DOI:https://doi.org/10.1007/s00396005046135. Pich A., Richtering W. Microgels by PrecipitationPolymerization: Synthesis, Characterization, andFunctionalization. In: Pich A., Richtering W. (eds.)Chemical Design of Responsive Microgels. SpringerHeidelberg Dordrecht London New York; 2011. p. 1–37.DOI: https://doi.org/10.1007/978-3-642-16379-136. Yamada N., Okano T., Sakai H., Karikusa F.,Sawasaki Y., Sakurai Y. Thermo-responsive polymericsurfaces; control of attachment and detachment ofcultured cells. Die Makromolekulare Chemie, RapidCommunications. 1990;11(11): 571–576. DOI: https://doi.org/10.1002/marc.1990.03011110937. Kushida A., Yamato M., Konno C., Kikuchi A.,Sakurai Y., Okano T. Decrease in culture temperaturereleases monolayer endothelial cell sheets togetherwith deposited fibronectin matrix from temperatureresponsiveculture surfaces. Journal of BiomedicalMaterials Research. 1999;45(4): 355–362. DOI: https://doi.org/10.1002/(sici)1097-4636(19990615)45:43.0.co;2-738. Sekine H., Shimizu T., Dobashi I., Matsuura K.,Hagiwara N., Takahashi M., et al. Cardiac cell sheettransplantation improves damaged heart function viasuperior cell survival in comparison with dissociatedcell injection. Tissue Engineering Part A. 2011;17(23-24): 2973–2980. DOI: https://doi.org/10.1089/ten.tea.2010.065939. Nishida K., Yamato M., Hayashida Y.,Watanabe K., Yamamoto K., Adachi E., et al. Corneal reconstruction with tissue-engineered cell sheetscomposed of autologous oral mucosal epithelium. TheNew England Journal of Medicine. 2004;351(12): 1187–1196. DOI: https://doi.org/10.1056/nejmoa04045540. Kanzaki M., Yamato M., Yang J., Sekine H.,Kohno C., Takagi R., et al. Dynamic sealing of lungair leaks by the transplantation of tissue engineeredcell sheets. Biomaterials. 2007;28(29): 4294–4302.DOI: https://doi.org/10.1016/j.biomaterials.2007.06.00941. Iwata T., Yamato M., Tsuchioka H., Takagi R.,Mukobata S., Washio K., et al. Periodontal regenerationwith multi-layered periodontal ligament-derived cellsheets in a canine model. Biomaterials. 2009;30(14):2716–2723. DOI: https://doi.org/10.1016/j.biomaterials.2009.01.03242. Sawa Y., Miyagawa S., Sakaguchi T., Fujita T.,Matsuyama A., Saito A., et al. Tissue engineeredmyoblast sheets improved cardiac function sufficientlyto discontinue LVAS in a patient with DCM: report ofa case. Surgery Today. 2012;42(2): 181–184. DOI:https://doi.org/10.1007/s00595-011-0106-443. Ohki T., Yamato M., Ota M., Takagi R.,Murakami D., Kondo M., et al. Prevention of esophagealstricture after endoscopic submucosal dissection usingtissue-engineered cell sheets. Gastroenterology.2012;143(3): 582–588. DOI: https://doi.org/10.1053/j.gastro.2012.04.05044. Ebihara G., Sato M., Yamato M., Mitani G.,Kutsuna T., Nagai T., et al. Cartilage repair intransplanted scaffold-free chondrocyte sheets usinga minipig model. Biomaterials. 2012;33(15): 3846–3851. DOI: https://doi.org/10.1016/j.biomaterials.2012.01.05645. Sato M., Yamato M., Hamahashi K., Okano T.,Mochida J. Articular cartilage regeneration using cellsheet technology. The Anatomical Record. 2014;297(1):36–43. DOI: https://doi.org/10.1002/ar.2282946. Kuramoto G., Takagi S., Ishitani K., Shimizu T.,Okano T., Matsui H. Preventive effect of oral mucosalepithelial cell sheets on intrauterine adhesions. HumanReproduction. 2014;30(2): 406–416. DOI: https://doi.org/10.1093/humrep/deu32647. Yamamoto K., Yamato M., Morino T.,Sugiyama H., Takagi R., Yaguchi Y., et al. Middle earmucosal regeneration by tissue-engineered cell sheettransplantation. NPJ Regenerative Medicine. 2017;2(1):6. DOI: https://doi.org/10.1038/s41536-017-0010-748. Gan D., Lyon L. A. Synthesis and Proteinadsorption resistance of PEG-modified poly(Nisopropylacrylamide) core/shell microgels.Macromolecules. 2002;35(26): 9634–9639. DOI: https://doi.org/10.1021/ma021186k49. Veronese F. M., Mero A. The impact ofPEGylation on biological therapies. BioDrugs.2008;22(5): 315–329. DOI: https://doi.org/10.2165/00063030-200822050-0000450. Sahay G., Alakhova D. Y., Kabanov A. V.Endocytosis of nanomedicines. Journal of ControlledRelease. 2010;145(3): 182–195. DOI: https://doi.org/10.1016/j.jconrel.2010.01.03651. Nolan C. M., Reyes C. D., Debord J. D.,García A. J., Lyon L. A. Phase transition behavior,protein adsorption, and cell adhesion resistance ofpoly(ethylene glycol) cross-linked microgel particles.Biomacromolecules. 2005;6(4): 2032–2039. DOI:https://doi.org/10.1021/bm050008752. Scott E. A., Nichols M. D., Cordova L. H., GeorgeB. J., Jun Y.-S., Elbert D. L. Protein adsorption and celladhesion on nanoscale bioactive coatings formed frompoly(ethylene glycol) and albumin microgels.Biomaterials. 2008;29(34): 4481–4493. DOI: https://doi.org/10.1016/j.biomaterials.2008.08.00353. South A. B., Whitmire R. E., García A. J.,Lyon L. A. Centrifugal deposition of microgels for therapid assembly of nonfouling thin films. ACS AppliedMaterials & Interfaces. 2009;1(12): 2747–2754. DOI:https://doi.org/10.1021/am900543554. Wang Q., Uzunoglu E., Wu Y., Libera M. Selfassembledpoly(ethylene glycol)-co-acrylic acidmicrogels to inhibit bacterial colonization of syntheticsurfaces. ACS Applied Materials & Interfaces. 2012;4(5):2498–2506. DOI: https://doi.org/10.1021/am300197m55. Wang Q., Libera M. Microgel-modified surfacesenhance short-term osteoblast response. Colloids andSurfaces B: Biointerfaces. 2014;118: 202–209. DOI:https://doi.org/10.1016/j.colsurfb.2014.04.00256. Tsai H.-Y., Vats K., Yates M. Z., Benoit D. S. W.Two-dimensional patterns of poly(N-isopropylacrylamide)microgels to spatially control fibroblastadhesion and temperature-responsive detachment.Langmuir. 2013;29(39): 12183–12193. DOI: https://doi.org/10.1021/la400971g57. Lynch I. , Miller I. , Gallagher W. M. ,Dawson K. A. Novel method to prepare morphologicallyrich polymeric surfaces for biomedical applicationsvia phase separation and arrest of microgel particles.The Journal of Physical Chemistry B. 2006;110(30):14581–14589. DOI: https://doi.org/10.1021/jp061166a58. Li Y., Chen P., Wang Y., Yan S., Feng X., Du W.,et al. Rapid assembly of heterogeneous 3D cellmicroenvironments in a microgel array. AdvancedMaterials. 2016;28(18): 3543–3548. DOI: https://doi.org/10.1002/adma.20160024759. Bridges A. W., Singh N., Burns K. L., BabenseeJ. E., Andrew Lyon L., García A. J. Reduced acuteinflammatory responses to microgel conformalcoatings. Biomaterials. 2008;29(35): 4605–4615. DOI:https://doi.org/10.1016/j.biomaterials.2008.08.01560. Bridges A. W., Whitmire R. E., Singh N.,Templeman K. L., Babensee J. E., Lyon L. A., et al.Chronic inflammatory responses to microgel-basedimplant coatings. Journal of Biomedical Materials Research Part A. 2010;94A(1): 252–258. DOI: https://doi.org/10.1002/jbm.a.3266961. Gutowski S. M., Templeman K. L., South A. B.,Gaulding J. C., Shoemaker J. T., LaPlaca M. C., et al.Host response to microgel coatings on neuralelectrodes implanted in the brain. Journal of BiomedicalMaterials Research Part A. 2014;102(5): 1486–1499.DOI: https://doi.org/10.1002/jbm.a.3479962. da Silva R. M. P., Mano J. F., Reis R. L. Smartthermoresponsive coatings and surfaces for tissueengineering: switching cell-material boundaries.Trends in Biotechnology. 2007;25(12): 577–583. DOI:https://doi.org/10.1016/j.tibtech.2007.08.01463. Schmidt S., Zeiser M., Hellweg T., Duschl C.,Fery A., Möhwald H. Adhesion and mechanicalproperties of PNIPAM microgel films and theirpotential use as switchable cell culture substrates.Advanced Functional Materials. 2010;20(19): 3235–3243. DOI: https://doi.org/10.1002/adfm.20100073064. Uhlig K., Wegener T., He J., Zeiser M., BookholdJ., Dewald I., et al. Patterned thermoresponsivemicrogel coatings for noninvasive processing ofadherent cells. Biomacromolecules. 2016;17(3): 1110–1116. DOI: https://doi.org/10.1021/acs.biomac.5b01728